2014
DOI: 10.5897/ijnam2014.0170
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of pregnant women in Ogun-East Senatorial Zone, Ogun State, Nigeria: A comparative study

Abstract: Poor maternal nutrition in pregnancy leads to increased morbidity and negative pregnancy outcomes including low birth weight and peri-natal mortality. Pregnancy places extra demands on the body systems of pregnant women, necessitating optimal intake of essential nutrients. Rural and urban disparities in nutritional status have been documented in literature. A cross-sectional comparative assessment of the dietary intake of 720 pregnant women accessing antenatal care at selected rural and urban primary health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
3
6
1
Order By: Relevance
“…In this study, income was significantly associated with food taboo. Pregnant women who earned 650-1000 birr were 56% less likely to have food taboo compared to pregnant women who have <650-birr monthly income, which is in line with the study done in Wondo Genet [12], Bangladesh [13], and Ogan state of Nigeria [14]. As income increases, the avoidance of food taboos decreases.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, income was significantly associated with food taboo. Pregnant women who earned 650-1000 birr were 56% less likely to have food taboo compared to pregnant women who have <650-birr monthly income, which is in line with the study done in Wondo Genet [12], Bangladesh [13], and Ogan state of Nigeria [14]. As income increases, the avoidance of food taboos decreases.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, our findings are indications that many infants in West Africa are not properly breastfed as long as exclusive breastfeeding is concern. Our findings are in corroboration with Horii et al (2017); Oluwole, Agboola, Onyibe, and Adeyoju (2016); Sholaye et al (2014); Bankole and Adetutu (2015) and UNICEF (2016) who empirically maintained that larger proportion of children born in Guinea, Nigeria and Sierra Leone were not exclusively breastfed as recommended by UNICEF/WHO.…”
Section: Discussionsupporting
confidence: 88%
“…In the West African region, prevalence of household poverty as well as the poor socioeconomic conditions of most women, absence of timely supports from relatives or partners negligence on the side of nursing mothers and the uncared-attitude by some healthcare workers, were amongst the leading threats that were restraining mothers from adhering to optimal breastfeeding (Andy, 2015;Hashim et al, 2017;World Health Organization, 2016). Indications from previous studies have clearly revealed that young children that were neither exclusively breastfed for a period of six months nor put to breast milk within an hour after birth were more susceptible to chronic and deadly infections than those that were optimally breastfed (Bisiriyu, Bankole, & Solanke, 2016;Derso, Biks, Tariku, & Tebeje, 2017;Sholaye, Badejo, & Jeminusi, 2014). Consequently, lifelong physical and cognitive impairments in growing children have been linked to improper and suboptimal breastfeeding practices among women (Aakre et al, 2017;Victora et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study in Hadiya, Southern Ethiopia also reported higher percentage (27%) of pregnant mother avoided some foods due to food taboos 21 . Another study in Nigeria also reported higher percentage (16.1%) of food taboo among rural pregnant women 22 . The possible reason for low percentage reported in the current study might be lower sample size than those studies.…”
Section: Discussionmentioning
confidence: 89%